Ipragliflozin improves the hepatic outcomes of patients with diabetes with NAFLD - Hirokazu Takahashi; Takaomi Kessoku; Miwa Kawanaka; Michihiro Nonaka; Hideyuki Hyogo; Hideki Fujii; Tomoaki Nakajima; Kento Imajo; Kenichi Tanaka; Yoshihito Kubotsu; Hiroshi Isoda; Satoshi Oeda; et al. (Сахарный диабет)
Sodium glucose cotransporter-2 inhibitors (SGLT2is) are now widely used to treat diabetes, but their effects on nonalcoholic fatty liver disease (NAFLD) remain to be determined. We aimed to evaluate the effects of SGLT2is on the pathogenesis of NAFLD. A multicenter, randomized, controlled trial was conducted in patients with type 2 diabetes with NAFLD. The changes in glycemic control, obesity, and liver pathology were compared between participants taking ipragliflozin (50 mg/day for 72 weeks; IPR group) and participants being managed without SGLT2is, pioglitazone, glucagon-like peptide-1 analogs, or insulin (CTR group). In the IPR group (n = 25), there were significant decreases in hemoglobin A1c (HbA1c) and body mass index (BMI) during the study (HbA1c, -0.41%, P < 0.01; BMI, -1.06 kg/m2, P < 0.01), whereas these did not change in the CTR group (n = 26). Liver pathology was evaluated in 21/25 participants in the IPR/CTR groups, and hepatic fibrosis was found in 17 (81%) and 18 (72%) participants in the IPR and CTR groups at baseline. This was ameliorated in 70.6% (12 of 17) of participants in the IPR group and 22.2 % (4 of 18). of those in the CTR group (P < 0.01). Nonalcoholic steatohepatitis (NASH) resolved in 66.7% of IPR-treated participants and 27.3% of CTR participants. None of the participants in the IPR group developed NASH, whereas 33.3% of the CTR group developed NASH. Conclusion: Long-term ipragliflozin treatment ameliorates hepatic fibrosis in patients with NAFLD. Thus, ipragliflozin might be effective for the treatment and prevention of NASH in patients with diabetes, as well as improving glycemic control and obesity. Therefore, SGLT2is may represent a therapeutic choice for patients with diabetes with NAFLD, but further larger studies are required to confirm these effects. (Hepatology Communications 2022;6:120-132) .Sodium glucose cotransporter-2 inhibitors (SGLT2is) are now widely used to treat diabetes, but their effects on nonalcoholic fatty liver disease (NAFLD) remain to be determined. We aimed to evaluate the effects of SGLT2is on the pathogenesis of NAFLD. A multicenter, randomized, controlled trial was conducted in patients with type 2 diabetes with NAFLD. The changes in glycemic control, obesity, and liver pathology were compared between participants taking ipragliflozin (50 mg/day for 72 weeks; IPR group) and participants being managed without SGLT2is, pioglitazone, glucagon-like peptide-1 analogs, or insulin (CTR group). In the IPR group (n = 25), there were significant decreases in hemoglobin A1c (HbA1c) and body mass index (BMI) during the study (HbA1c, -0.41%, P < 0.01; BMI, -1.06 kg/m2, P < 0.01), whereas these did not change in the CTR group (n = 26). Liver pathology was evaluated in 21/25 participants in the IPR/CTR groups, and hepatic fibrosis was found in 17 (81%) and 18 (72%) participants in the IPR and CTR groups at baseline. This was ameliorated in 70.6% (12 of 17) of participants in the IPR group and 22.2 % (4 of 18). of those in the CTR group (P < 0.01). Nonalcoholic steatohepatitis (NASH) resolved in 66.7% of IPR-treated participants and 27.3% of CTR participants. None of the participants in the IPR group developed NASH, whereas 33.3% of the CTR group developed NASH.Conclusion: Long-term ipragliflozin treatment ameliorates hepatic fibrosis in patients with NAFLD. Thus, ipragliflozin might be effective for the treatment and prevention of NASH in patients with diabetes, as well as improving glycemic control and obesity. Therefore, SGLT2is may represent a therapeutic choice for patients with diabetes with NAFLD, but further larger studies are required to confirm these effects. (Hepatology Communications 2022;6:120-132) .